Pengembangan Desa Benteng Sebagai Desa Wisata Berbasis Agro di Masa Pandemi Covid-19 - Untari, Rini; Faturokhman, Muh; Priatna, Wahyu Budi; Santoso, Hudi (Institut Pertanian Bogor, 2023)
This community service was carried out as an effort to revive the tourism sector by developing an agro-based tourism village in Benteng Village by identifying the perceptions of tourism village managers, constraints and impacts, and program sustainability. This activity seeks to construct perceptions of agro-tourism activities, media promotion, and the development of agro-based tourism. The readiness of managers to become part of the identified consists of long-time readiness to receive visitors, service ethics to visitors, aspects of security, comfort, and cleanliness as well as readiness for agro-tourism activities. Data collection was carried out through literature, participatory studies, interviews, and distributing questionnaires with a purposive sampling technique to 18 respondents managing the Benteng tourism village. Data analysis used descriptive quantitative and descriptive qualitative methods. Based on the assessment of the Benteng Village manager, harvesting activities, enjoying the landscape, photography, interpretation programs, and shopping for agricultural products are agro-based tourism activities that can be carried out in Benteng Village. Promotional videos are the highest choice for promoting village potential and managers say they are ready to receive visitors 1‒3 hours and a week. The manager also stated that he was ready regarding the ethics of service to visitors, security, comfort, and cleanliness including implementing health protocols (prokes) and being ready to develop agro-tourism activities. Implementation constraints are technical in nature and post-pandemic conditions that require adjustments in various aspects. Development of tourism potential through an integrated approach by collaborating involving various parties including universities as well as massive promotion using the right media so that agro-based tourism activities in Benteng Village can be sustainable.